A comparison of urban restoration of heritage buildings: a case study in Arnavutköy, Istanbul and George Town, Penang - Sophian, Nur Sofia Hanim; Nazry, Syaza Farzana; Ibrahim, Illyani (IIUM Press, 2023)
This research presents a comparative analysis of heritage building urban restoration in Arnavutkoy, Istanbul and George Town, Penang. The method of this study is using observation and review method. This study also analyses on the restoration, community involvement, and the preservation architectural heritage to unveils unique stategies employed in each site. The findings contribute valuable insights to the field of heritage conservation and urban development, aiding in the formulation of effective restoration approaches for diverse cultural contexts.